Dinâmica espacial, migração e preferência de micro-hábitat de Aegla longirostri bond-buckup e buckup, 1994 (crustacea, anomura, aeglidae) - Baumart, Joele Schmitt (2014)
Understanding the population dynamic processes is fundamental to access its viability (health). Great part of these processes is closely related to the organism densities in a studied population. These data can reveal how the population is arranged in the environment and, in adverse conditions, it is possible to forecast the occurrence of dispersion/migration. This study aims to investigate some ecological parameters of an Aegla longirostri population, a freshwater anomuran from the southern Brazil: (i) to estimate the population density, (ii) the substrate preference, (iii) the home range and (iv) the possible dispersion patterns. The study site was the first order stream Sanga do Caranguejo, located in the central region of Rio Grande do Sul State, during 2010 and 2011. For population density and dispersion investigation covo traps were used, distributed through the stream, in different times in the year. The study of the substrate preference used PVC gutters covered by mesh and arranged on the stream substrate, with controlled density population; a surber was used for active search in the stream. The home range analysis used radio telemetry techniques. The population size was estimated in 950 individuals in spring and 210 in autumn (estimated according to the Bayesian Method). With respect to the substrate preference, we found that there is an ontogenetic association regarding the choice. The juveniles, in the first development stages, prefer sandy substrates, while adults (males and females) prefer more complex substrates. The estimates of home range of eglids vary between 8,41 to approximately 45,49 linear meters of stream, and these crustaceans showed the local dislocation, once they perform their activities around a specific point in the stream. To finalize, we identified that the juveniles and adults of eglids are active walkers, not being carried by the flow in a passive way as occurs in larvae stage in other crustaceans. Its activities are related to the environment temperature and density of adult males. We believe that the knowledge about the group has increased, however, as it is a complex group, with a rich evolutionary history, much remain to be investigated about these freshwater crustaceans.